Looking under the hood: A comparison of techno-economic assumptions across national and global integrated assessment models. (1st April 2019) - Krey, Volker; Guo, Fei; Kolp, Peter; Zhou, Wenji; Schaeffer, Roberto; Awasthy, Aayushi; Bertram, Christoph; de Boer, Harmen-Sytze; Fragkos, Panagiotis; Fujimori, Shinichiro; He, Chenmin; Iyer, Gokul; et al.
Abstract: Integrated assessment models are extensively used in the analysis of climate change mitigation and are informing national decision makers as well as contribute to international scientific assessments. This paper conducts a comprehensive review of techno-economic assumptions in the electricity sector among fifteen different global and national integrated assessment models. Particular focus is given to six major economies in the world: Brazil, China, the EU, India, Japan and the US. The comparison reveals that techno-economic characteristics are quite different across integrated assessment models, both for the base year and future years. It is, however, important to recognize that techno-economic assessments from the literature exhibit an equally large range of parameters as the integrated assessment models reviewed. Beyond numerical differences, the representation of technologies also differs among models, which needs to be taken into account when comparing numerical parameters. While desirable, it seems difficult to fully harmonize techno-economic parameters across a broader range of models due to structural differences in the representation of technology. Therefore, making techno-economic parameters available in the future, together with of the technology representation as well as the exact definitions of the parameters should become the standard approach as it allows an open discussion of appropriate assumptions. Highlights: Comparison of technology representation and techno-economic parameters of 15 IAMs. Structural differences in representing technology in IAMs are identified. Methods of projecting techno-economic parameters differ across IAMs. Strict harmonization of techno-economic parameters across models is difficult. Recommendation to publish techno-economic parameters and technology representation.